Atividade fitotóxica de Serjania lethalis A. St.-Hil. e Sapindus saponaria L. (Sapindaceae) e identificação de metabólitos secundários - Grisi, Patricia Umeda (2015)
The organization and dynamic of community are determined, among other factors, by the balance of positive and negative interactions of species. Research of plants with allelopathic activity comes from the need to introduce new alternatives in the management of agricultural pests. Species of Sapindaceae family are rich source of phytochemicals and have a huge potential for the production of secondary compounds with biopesticide activity. This study attempted to clarify the following issues: (1) leaves and stems/bark extracts of Serjania lethalis A. St.-Hil. and Sapindus saponaria L. could interfere in the diaspores germination and seedling growth of sesame (Sesamum indicum L.), radish (Raphanus sativus L.), wheat (Triticum aestivum L.)? (2) In addition, these extracts could affect the development of wild poinsettia (Euphorbia heterophylla L.) and barnyardgrass (Echinochloa crus-galli (L.) P. Beauv.), allowing thus the control of these weeds? (3) The fractionated extracts from S. saponaria could present insecticidal activity against the mortality of Toxoptera citricidus Kirkaldy (Homoptera: Aphididae) adults and nymphs? (4) Among the active extracts, which is most promising for start a bioprospecting, allowing isolate and identify the compounds present? To answer these questions bioassays were performed with ethanol or aqueous crude extract (2.5, 5.0, 7.5 and 10%, w/v) and tested with fractionated extract by liquid-liquid partition using hexane, ethyl acetate (EtOAc) and butanol. Leaf and stem/stem bark extracts of S. lethalis and S. saponaria were phytotoxic and inhibited the process of germination and seedling growth of weeds and cultivated species, showing concentration-dependent effect. The phytotoxic effect of the extracts ranged according to the receptor species, and, in most cases, the leaf extract showed greater inhibitory activity. For some variables, this effect was similar and even superior to commercial herbicide. One of the action modes was observed in root growth of sesame and wild poinsettia seedlings, wherein the extract caused a significant decrease in elongation of metaxylem cells. The EtOAc fraction from the ethanol extract of S. saponaria leaves showed inhibitory effect greater than the hexane fraction on the development of barnyardgrass and wild poinsettia seedlings. The phytochemical study of this fraction resulted in the isolation of 3-(1,2-dimethyl-5-oxabicyclo [2.1.1] hexan-2-yl) but-2-enoic acid, a monoterpene acid with spectroscopic characteristics not known in the literature. This compound also inhibited the germination and growth of weeds; however, the EtOAc fraction was more active in reducing seedlings growth. The hexane fraction from the ethanol extract of S. saponaria leaves showed phytotoxic effect on elongation of wheat coleoptile and caused high mortality of T. citricidus nymphs and adults. The main substances 22 identified in this fraction were flavonols derivative of kaempferol and quercetin, and these may be involved in the biological activity observed. Thus, S. saponaria may be a donor species of compound with insecticide and herbicide potential, and a good candidate to supply allelochemicals for future use in agriculture.